Radix Glycyrrhizae extract and licochalcone a exert an anti-inflammatory action by direct suppression of toll like receptor 4. (10th February 2023) - Cai, Min; Xu, You-cai; Deng, Bo; Chen, Jun-Bang; Chen, Ting-Fang; Zeng, Ke-Feng; Chen, Si; Deng, Sui-hui; Tan, Zhang-bin; Ding, Wen-jun; Zhang, Shuang-wei; Liu, Bin; et al.
Abstract: Ethnopharmacological relevance: Radix Glycyrrhizae (GL), a herbal medicine that is widely available, has shown advantages for a variety of inflammatory diseases. Toll like receptor 4 (TLR4) pathway has been shown to play a key role in the progression of inflammation. Aim of the study: The purpose of this study was to investigate the involvement of TLR4 in the anti-inflammatory mechanism of GL extract and its active constituent on acute lung injury (ALI). Materials and methods: A model of inflammation produced by lipopolysaccharide (LPS) was established in C57BL/6 mice and macrophages derived from THP-1. To screen the active components of GL, molecular docking was used. Molecular dynamics and surface plasmon resonance imaging (SPRi) were used to study the interaction of a specific drug with the TLR4-MD2 complex. TLR4 was overexpressed by adenovirus to confirm TLR4 involvement in the anti-inflammatory activities of GL and the chosen chemical. Results: We observed that GL extract significantly reduced both LPS-induced ALI and the production of pro-inflammatory factors including TNF-α, IL-6 and IL-1β. Additionally, GL inhibited the binding of Alexa 488-labeled LPS (LPS-488) to the membrane of THP-1 derived macrophages. GL drastically reduce on the expression of TLR4 and the activation of mitogen-activated protein kinases (MAPKs) and nuclear factor-B (NF-κB). Furthermore, molecular docking revealed that Licochalcone A (LicoA) docked into the LPS binding site of TLR4-MD2 complex. MD2-LicoA binding conformation was found to be stable using molecular dynamic simulations. SPRi indicated that LicoA bound to TLR4-MD2 recombinant protein with a KD of 3.87 × 10 −7  M. LicoA dose-dependently reduced LPS-488 binding to the cell membrane. LicoA was found to significantly inhibit LPS-induced lung damage and inflammation. Furthermore, LicoA inhibited TLR4 expression, MAPK and NF-κB activation in a dose-dependent manner. The inhibitory effects of GL and LicoA on LPS-induced inflammation and TLR4 signaling activation were partly eliminated by TLR4 overexpression. Conclusion: Our findings imply that GL and LicoA exert inhibitory effects on inflammation by targeting the TLR4 directly. Graphical abstract: Image 1